Analysis of physiological and biochemical changes and metabolic shifts during 21-Day fasting hypometabolism - Zhongquan Dai; Hongyu Zhang; Xiukun Sui; Feng Wu; Cheng Zhang; Zhiqi Fan; Hailong Wang; Yaxiu Guo; Chao Yang; Siyu Jiang; Linjie Wang; Bingmu Xin; et al. (Scientific Reports)
Abstract This study aimed to evaluate the impact of prolonged fasting on the physiological and biochemical alterations and metabolic shifts in healthy adults and to provide experimental data and theoretical support for the hypometabolic state induced by prolonged fasting. Thirteen volunteers were selected through public recruitment to undergo a 21-day complete fasting experiment. The experimental period lasted 34 days, including a 3-day baseline, 21-day completing fasting, 5-day calorie restriction and 5-day full recovery diet. Physiological indicators such as body weight, blood pressure, blood glucose, blood ketones, and blood uric acid were evaluated along with resting metabolic rate, routine blood tests, liver function, and heart function indexes employing traditional approaches. During the 21-day complete fasting period, there was a significant decrease in body weight (average − 14.96 ± 1.55%), a reduction in blood glucose (average − 21.63 ± 0.058%), an increase in blood ketones (from baseline 0.1 ± 0.04 mmol/L to 6.61 ± 1.25 mmol/L) and blood uric acid (from baseline 385.38 ± 57.78 µmol/L to 866.31 ± 172.01 µmol/L), a continuous decline in resting energy expenditure (average − 20.3 ± 11.13%), and the respiratory quotient tending towards fat metabolism. Most of the items in the complete blood count and liver indicators remained stable and within the normal range. Heart function showed functional adaptive changes without structural damage. Prolonged fasting can reduce the body’s resting energy expenditure and adapt to body weight loss through physiological regulatory mechanisms without adverse effects on basic physiological functions or the structure of important organs. Under medical supervision, healthy adults can safely engage in prolonged fasting for up to 21 days with metabolic adaption and no damage to pivotal organ, which could provide potential technical support for human health and survival strategies in extreme conditions such as food shortages during long-duration manned spaceflight.